Health effects of exposure to EMF (Brussels, 2009)
"Due to rapid technological advances and new scientific research, the Commission asked the Committee to update its opinion from 21 March 2007. The update considered more than 200 new scientific papers yet the conclusions differ little from the earlier opinion. Based on current evidence the main conclusions remain that radio frequency fields used in wireless communication technologies are unlikely to lead to an increase in cancer in the human population at large. However, further studies are needed to clarify if long-term exposure to mobile phones (well beyond 10 years) increases cancer risk for an individual using a mobile phone frequently and to examine the effects on children. The Commission has committed research funds from the 7th research framework programme to investigate the link between mobile phones and brain cancer risk in children. Data for health effects of intermediate frequency fields used, for example, in metal detectors or anti theft devices in shops, are still lacking. This area of research is important given the increasing exposure to these products and will thus need to be continued. The updated opinion confirms the 2007 opinion that extremely low frequency fields, used in high voltage power lines might contribute to childhood leukaemia. Furthermore, the updated opinion identified 2 new epidemiological studies that indicate a possible link to Alzheimer's disease. These are serious matters and further investigation will be pursued. (...)"